Integrative Analysis of the DICER-like (DCL) Genes From Peach (Prunus persica): A Critical Role in Response to Drought Stress - Belal, Mohammad A.; Ezzat, Mohamed; Zhang, Yuanqiang; Xu, Ziang; Cao, Yunpeng; Han, Yuepeng (Frontiers in Ecology and Evolution, 2022)
DICER-likes (DCLs) proteins are the core component for non-coding RNA (ncRNA) biogenesis, playing essential roles in some biological processes. The DCL family has been characterized in model plants, such as Arabidopsis, rice, and poplar. However, the evolutionary aspect and the expression mechanism under drought stress were scarce and have never been reported and characterized in one of the most important worldwide cultivated fruit trees, peach (Prunus persica). Eight DCLs genes in the Prunus persica genome were detected, in addition to 51 DCLs in the other seven Rosaceae genomes. The phylogenetic analysis with Arabidopsis thaliana and RTL1 gene as outgroups suggested that DCL members are divided into four clades: DCL1, DCL2, DCL3, and DCL4 with several gene gain/loss events of DCL gene copies through the evolutionary tract of the Rosacea family. The number of homologous DCL copies within each clade, along with the chromosomal location indicated gene duplication event of the DCL2 gene occurred once for the subfamily Amygdaloideae and twice for Pyrus communis and Prunus dulics and trice for the P. persica on Chromosome number 7 genes. Another duplication event was found for the DCL3 gene that occurred once for all the eight Rosaceae species with no match in A. thaliana. The DCL genetic similarity and activity was evaluated using BLASTp and previously published RNA-seq data among different tissues and over different time points of peach trees exposed to drought conditions. Finally, the expression pattern of PrupeDCLs in response to drought stress was identified, and two of these members, Prupe.7G047900 and Prupe.6G363600, were found as main candidate genes for response to drought stress. Our data presented here provide useful information for a better understanding of the molecular evolution of DCL genes in Rosaceae genomes, and the function of DCLs in P. persica.